Self-Docking Characteristics and Sliding Mode Control on Space Electromagnetic Docking Mechanism - Boyu Wei; Jie Zhang; Ning Kong; Shuai Ma; Bo Wang; Runqi Han (Machines, 2023)
Electromagnetic docking technology can realize the flexible docking and safe separation of spacecraft, and presents broad application prospects. However, an electromagnetic force with nonlinearity and uncertainty properties increases the difficulties of the electromagnetic docking control. In this work, the magnetic dipole far-field model of a single coil has been established by simplifying the electromagnetic docking device. Afterward, the electromagnetic force and electromagnetic torque models were obtained during space electromagnetic docking. The space electromagnetic docking dynamics model was established by analyzing the influences of disturbance force and disturbance torque caused by a geomagnetic field. According to the one-dimensional docking reference trajectory, the sliding mode variable structure controllers based on exponential reaching law were proposed and verified. The quasi-sliding mode control method has been adopted to solve the chattering problem in sliding mode variable structure control. The simulation results show that it is necessary to design and add an electromagnetic controller to achieve flexible docking. The sliding mode variable structure controller based on quasi sliding mode can realize one-dimensional electromagnetic flexible docking, and have made good tracking effect on the reference trajectory. Compared with the control method based on exponential reaching law, it can reduce the chattering phenomenon in the control process. The sliding mode variable structure control strategy based on quasi sliding mode presented good robustness. Therefore, it can provide theoretical guidance and control reference for the flexible docking process between electromagnetic satellites.